Challenges and Opportunities for the EU Common Fisheries Policy Application in the Mediterranean and Black Sea - Cosimo Solidoro (Frontiers Research Topics, 2019)
The application of the Common Fisheries Policy (CFP) in the Mediterranean and Black Sea faces several challenges also because of large ecological, economic, political and institutional differences across the basin. The challenge of CFP application is exacerbated by the legal/administrative situation, with large areas outside national/EU jurisdictions, by the different development of fisheries that result in fleet capacities highly different on opposite shores of some sub-basins, as well as by uneven monitoring and data availability across the basins that result in situations that hamper sustainable management. This book collates analyses related to the application of the principles included in the CFP in Mediterranean and Black Sea, including assessments of current status, scenario analyses, visions of best solutions, evaluation of critical hot spots and effects of regionalization of fisheries management. The eBook tackles from local to transboundary issues and solutions and provides a broad vision of problems together with important practical solutions for CFP application in the Mediterranean and Black Sea.